STATE VS UMRAH PILGRIMS: BETWEEN JUSTICE OR BENEFIT (JUDGMENT OF THE SUPREME COURT JUDGE AGAINST THE CONFISCATION OF PT. FIRST TRAVEL'S ASSETS) - Waldi Nopriansyah; Muzalifah Muzalifah (Jurnal Cendekia Hukum, 2022)
Fraud cases committed by PT. First Anugerah Karya Wisata (PT. First Travel) had shocked the people of Indonesia. There are 63,000 Umrah pilgrims deceived by PT. First travel. The interesting thing about this case, where the judge decided to seize the assets of PT. First Travel. This decision is a pro and contra in the community considering that the assets are sourced from the funds of the Umrah pilgrims. Therefore, this article discusses the judge's decision on the seizure of assets of PT. First Travel. This type of research is qualitative in the form of literature research with a normative juridical approach. The author concludes that the judge's decision on the seizure of assets of PT. First Travel prioritizes the value of benefit but does not ignore the value of justice. The form of benefit value in this decision is where the judge considers the great risk to the victims of the congregation if the assets are distributed. Therefore, the judge decided to seize the assets of PT. First Travel for the public interest or the benefit of the wider community.